2007
DOI: 10.1590/s1517-86922007000200006
|View full text |Cite
|
Sign up to set email alerts
|

Influência do nível de atividade física sobre a aptidão cardiorrespiratória em mulheres idosas

Abstract: As age progresses, a decrease of daily activities and reduction of functionality where the cardiorespiratory capacity may be considered one of the most affected components, is faced. The aim of this study was to examine the association between level of physical activity and cardiorespiratory capacity in older women. Nine hundred and sixty women age above 60 years, non-institutionalized, divided in five age groups were evaluated: F1 (60-64 years; n = 286); F2 (65-69 years; n = 295); F3 (70-74 years; n = 207); F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
26

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 23 publications
(52 reference statements)
0
6
0
26
Order By: Relevance
“…3,11,13 The results of the present study indicate that elderly women who regularly practiced physical exercise suffered a lesser decline in CRF than their inactive peers. It was also observed that the CRF level of the active group during reassessment (480.8 m) was similar to that found in the inactive group during the first assessment (484.9 m), indicating that elderly persons who fulfilled PRE recommendations maintained levels of fitness of 5.8 years earlier than their inactive peers.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…3,11,13 The results of the present study indicate that elderly women who regularly practiced physical exercise suffered a lesser decline in CRF than their inactive peers. It was also observed that the CRF level of the active group during reassessment (480.8 m) was similar to that found in the inactive group during the first assessment (484.9 m), indicating that elderly persons who fulfilled PRE recommendations maintained levels of fitness of 5.8 years earlier than their inactive peers.…”
Section: Resultsmentioning
confidence: 52%
“…In contrast, a cross-sectional study by Krause et al 3 analyzed the decline in CRF of 960 elderly women, grouped into age groups with intervals of five years (60 to <80 years). CRF was evaluated by the six-minute walk test (6MWT).…”
Section: Discussionmentioning
confidence: 99%
“…Desse modo, seria razoável pensar que as idosas do GE teriam se beneficiado dos efeitos da prática regular de exercícios físicos (9,10,24) . Além disso, as idosas fisicamente ativas percorreram a distância com menor FC absoluta (GNE = 119 ± 17bpm vs. GE = 113 ± 22bpm) e menor percentual representativo da FCmáx (GNE = 77 ± 9,9bpm vs. GE = 74 ± 12,6bpm), apesar de diferenças significativas não terem sido constatadas para essas variáveis.…”
Section: Discussionunclassified
“…El sistema cardiorrespiratorio es uno de los más 12 afectados en los ancianos . Esto es también un reflejo de 9 la falta de actividad física .…”
Section: Introductionunclassified
“…Esto es también un reflejo de 9 la falta de actividad física . Con el aumento de la edad, hay una disminución en la captación y el transporte de oxígeno, generando un déficit en la demanda metabólica, influyendo negativamente sobre la resistencia 12 cardiorrespiratoria del anciano . Este sistema sufre varias alteraciones, de las cuales las más notorias son la disminución de la frecuencia cardiaca, el aumento del volumen diastólico final y el volumen sistólico para que haya manutención de débito cardíaco, aumento de la 8 presión arterial sistólica y diastólica .…”
Section: Introductionunclassified